A case with good response to belimumab for lupus nephritis complicated by IgG4-related disease. (May 2019) - Yamamoto, M; Aochi, S; Suzuki, C; Nakamura, S; Murakami, R; Ogawa, Y; Takahashi, H
Immunoglobulin (Ig)G4-related disease (IgG4-RD) is an unusual complication of systemic lupus erythematosus (SLE). We report a case in which belimumab proved efficacious for not only SLE, but also IgG4-RD. A 58-year-old Japanese woman had suffered from photodermatosis and erythema on the limbs for 20 years. She presented in slight fever and fatigue since 2016. Laboratory data showed hypergammaglobulinemia, proteinuria and positive results for anti-nuclear antibody and anti-double-stranded DNA antibody. Furthermore, elevated levels of serum IgG4 were detected. Contrast-enhanced computed tomography disclosed multiple areas of poor enhancement in the kidneys. The patient was diagnosed with lupus nephritis and IgG4-RD from renal biopsy. Treatment was started with prednisolone at 40 mg/day and mycophenolate mofetil. Proteinuria and serological findings improved initially, but tapering the dose of glucocorticoid proved difficult. After treatment was started with belimumab, clinical symptoms and proteinuria resolved completely. The dose of glucocorticoid was successfully tapered and serum concentration of IgG4 fell further. This appears to represent the first report of a case in which both SLE and IgG4-RD were effectively treated using belimumab.